2022
DOI: 10.1039/d2ta01186g
|View full text |Cite
|
Sign up to set email alerts
|

A single-crystal nickel-rich material as a highly stable cathode for lithium-ion batteries

Abstract: The commonly used polycrystalline Ni-rich LiNi0.8Co0.1Mn0.1O2 (NCM811) cathode materials suffer from the electrochemical degradation such as rapid impedance growth and capacity decay due to their intrinsically vulnerable grain-boundary fracture during...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…66,68,128,[184][185][186][187][188][189] Recently, several efforts have already been made to produce single crystal NCMs with a higher Ni-content and to compare the performance with the polycrystalline one. [190][191][192][193][194][195][196][197][198][199][200][201][202] As an example, Ran et al have shown that single crystal NCM811 is superior in terms of cycling as well as rate performance compared to the polycrystalline one. 190 Recently, Kim et al have synthesized three different single crystal high-Ni NCMs, having a similar particle size distribution and morphology, such as LiNi 0.8 Mn 0.1 Co 0.1 O 2 , LiNi 0.80 Mn 0.15 -Co 0.05 O 2 , and LiNi 0.85 Mn 0.10 Co 0.05 O 2 by the co-precipitation method in the presence of poly(vinylpyrrolidone) (PVP) followed by calcination and analyze their chemical, electrochemical and thermal properties.…”
Section: Single Crystal Cathodesmentioning
confidence: 99%
See 1 more Smart Citation
“…66,68,128,[184][185][186][187][188][189] Recently, several efforts have already been made to produce single crystal NCMs with a higher Ni-content and to compare the performance with the polycrystalline one. [190][191][192][193][194][195][196][197][198][199][200][201][202] As an example, Ran et al have shown that single crystal NCM811 is superior in terms of cycling as well as rate performance compared to the polycrystalline one. 190 Recently, Kim et al have synthesized three different single crystal high-Ni NCMs, having a similar particle size distribution and morphology, such as LiNi 0.8 Mn 0.1 Co 0.1 O 2 , LiNi 0.80 Mn 0.15 -Co 0.05 O 2 , and LiNi 0.85 Mn 0.10 Co 0.05 O 2 by the co-precipitation method in the presence of poly(vinylpyrrolidone) (PVP) followed by calcination and analyze their chemical, electrochemical and thermal properties.…”
Section: Single Crystal Cathodesmentioning
confidence: 99%
“…[190][191][192][193][194][195][196][197][198][199][200][201][202] As an example, Ran et al have shown that single crystal NCM811 is superior in terms of cycling as well as rate performance compared to the polycrystalline one. 190 Recently, Kim et al have synthesized three different single crystal high-Ni NCMs, having a similar particle size distribution and morphology, such as LiNi 0.8 Mn 0.1 Co 0.1 O 2 , LiNi 0.80 Mn 0.15 -Co 0.05 O 2 , and LiNi 0.85 Mn 0.10 Co 0.05 O 2 by the co-precipitation method in the presence of poly(vinylpyrrolidone) (PVP) followed by calcination and analyze their chemical, electrochemical and thermal properties. 191 From their study, it was observed that the presence of Ni 3+ in higher amounts reduces the thermal and air stability of higher Ni-content single crystal NCMs, whereas Mn improves all kinds of stability.…”
Section: Single Crystal Cathodesmentioning
confidence: 99%
“…The active material will nally turn into an insulating rock-salt NiO phase, accompanied by gas emission. 14,15 Thus, suppressing microcrack generation has been considered a key solution for alleviating the rapid capacity decay of Ni-rich cathode materials.…”
Section: Introductionmentioning
confidence: 99%
“…SC material maintains high particle integrity and Li + transport capacity as a result of its small particle size and single grain boundary . It has been demonstrated that SC material has stronger resistance to high pressure and temperature and is superior to conventional PC material NCM in terms of cycling stability and storage conditions. However, the low diffusion efficiency of Li + in micrometer-sized particles deteriorates the rate performance of the SC material, while the long-term cycling stability comes at the expense of high capacity. , …”
Section: Introductionmentioning
confidence: 99%